The Union Wage Effect Re-Examined - Maki, Dennis; Christensen, Sandra (Relations industrielles / Industrial Relations, 1980)
In this paper, the authors extend the literature on union wage effect in two ways. They use aggregate industry data in a simultaneous-equations model to provide an estimate for the union wage effect in Canada which recognizes the endogenity of union coverages. And they suggest a possible cause for the difference in results obtained for the U.S. by Ashenfelter and Johnson, on the one hand, and Kahn on the other.